Psychotherapy training via a task‐based assessment of the multicultural orientation framework: A pilot study. - Stewart, Shaakira Haywood; Drinane, Joanna M.; Owen, Jesse; Dumas, Denis (Counselling & Psychotherapy Research, 2024)
This pilot study involved the development and initial testing of an applied Multicultural Orientation Performance Task (MCO‐PT) and coding system. The MCO‐PT was comprised of seven brief video simulations of cultural exchanges. Seventy‐four graduate students recorded responses and then completed measures of desirable responding and multicultural competence. Research assistants coded the videos on three dimensions: cultural humility, cultural opportunities and cultural comfort (ICCs 0.61–0.97). Exploratory factor analysis yielded three factors that corresponded with the MCO constructs (alphas 0.77–0.97). Cultural opportunities were positively correlated with multicultural competence, and none of the subscales were associated with social desirability.